Hybrid financing instruments : analyzing investors’ reactions to the issuance of convertible bonds - Busch, Rebecca Sabrina (2022)
Convertible bonds have become increasingly popular over the past years. However, there is still no clear consent about why companies issue convertible bonds and how investors perceive companies who issue them. This research aims to provide more insights into the investors’ perspective. Thereby, interviews with European convertible bond investors and an event study based in Europe are conducted. The findings make clear that investors have different perceptions and do not agree with all theories. Nonetheless, they provide more insights into investors’ reactions to the issuance of convertible bonds which can be helpful for companies as they can understand which signals they send. In particular, the research shows that green convertible bonds are becoming increasingly important for investors. Furthermore, the event study shows that there is a clear difference between mature and growth companies that issue convertible bonds. The market reacts negatively to the issuance of both companies, however for growth companies, this effect is only temporary while for mature companies it continues. Additionally, mature companies already performed worse before the issuance in terms of cumulative average abnormal returns than growth companies. Overall, this research provides more insights into investors’ perceptions and helps companies to understand which signals their issuance of convertible bonds sends.